Evaluation of Experimental Zoysiagrasses in Southern Kansas - L. Parsons; J. Fry (Kansas Agricultural Experiment Station Research Reports, 2015)
Kansas State University has been cooperating with Texas A&M AgriLife Research – Dallas to identify zoysiagrasses that are superior in quality to ‘Meyer,’ the industry standard, and that have equivalent or better freeze tolerance. Six of eight experimental crosses between selectZoysiacultivars were established in Wichita, Kansas, in 2009 and since that time have had consistently superior ratings in three or more measures.
Keywords: Turfgrass; zoysiagrass; & #x27; Meyer& #x27; zoysiagrass; Zoysia japonica; Z. matrella; & #x27; Emerald& #x27; zoysiagrass